FREQUENCY OF DIFFERENT INDICATIONS FOR ENDODONTIC TREATMENT AMONG PATIENTS FROM PANCEVO, SERBIA - Tomić, Marija; Kolak, Veljko (Medicinski podmladak, 2021)
Introduction: Despite great efforts to develop preventive measures, among the most common reasons why patients visit their dentist still are conditions that require endodontic treatment. Important role in maintaining oral health plays on time and high quality endodontic treatment. Aim: The aim of this epidemiological study was to evaluate the prevalence of teeth indicated for endodontic treatment and to investigate the frequency of different indications for therapy in an adult population of municipality of Pancevo, Serbia. Material and methods: Investigations were conducted on a sample of patients who referred for dental examination and treatment, at the Department of Restorative dentistry and Endodontics, Faculty of Dentistry in Pancevo, during 2018. The study included 229 male and female subjects, aged over 18, who had at least one tooth indicated for endodontic treatment. Subjects were clinically examined by a standardized procedure, using visual and tactile inspection, percussion and palpation tests, periodontal evaluation and pulp vitality tests. Panoramic and retroalveolar radiographs were also analyzed.  Data were statistically analyzed using Chi-Square test.   Results: Endodontic treatment was indicated on 322 teeth from total number of 4911 (6.6%). Largest frequency of teeth indicated for treatment was recorded among subjects aged over 60 years (7.5%) and on frontal teeth (36.6%). The most commonly registered indications were asymptomatic irreversible pulpitis (32.3%) and symptomatic irreversible pulpitis (19.9%). Irreversible pulpitis was the most common indication for endodontic treatment between all age groups of subjects, between both genders and between all three teeth functional groups (p˂0.001).   Conclusion: Percentage of teeth indicated for endodontic treatment was higher than presented in other studies. Irreversible pulpitis was the most common indication for endodontic treatment. After conducting the study it is clear that dental care and caries preventive programs should be strengthened and expanded, especially among people with less education and awareness regarding dental health.   Keywords: indications for endodontic treatment, irreversible pulpitis, pulp necrosis